New Distribution of the Panama Humming Frog (Elachistocleis panamensis), in the Azuero Region, Panama: Nueva distribución del sapo colibrí panameño (Elachistocleis panamensis), en la región de Azuero, Panamá - González-Pinzón , Macario; Urriola , Mario; Romero, Angel (Revista Científica Vida Natural, 2025)
The research focused on the study of the frog belonging to the Microhylidae family, distributed in South and Central America. In November 2021, two observations were made in Pedasí, Los Santos province, within the Azuero Dry Arc, where an individual was collected that was later identified as Elachistocleis panamensis. This record expands the known distribution range of the species, locating it approximately 90 km by land southwest of its last known position.